Flexible Quarter-Wave Controlled Power Transmission - G. E. Pospelov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
An analysis of a quarter-wave power transmission has been carried out. The paper demonstrates its application. It is recommended to use a STATKON system of serial-type in order to control it.